1987
DOI: 10.1515/znc-1987-9-1004
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Caffeic Acid Derivative and Other Constituents of Populus Bud Excretion and Propolis (Bee-Glue)

Abstract: E ck h a rd W ollenw eber, Y oshinori A sakaw a*, D etlef Schillo, U lrich L eh m an n , and H eid ru n W eigelThe bud exudates of Populus nigra, P. trichocarpa, and P. grandidentata x tremuloides were analyzed for the presence of phenolics and flavonoids. A novel natural product, caffeic acid y.ydimethylallyl ester, was identified from P. nigra, along with further phenolics such as /?-hydroxyacetophenone, dimethyl caffeic acid, cinnamoyl cinnamata and vanillin. The flavonoid aglycones correspond to those repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
2

Year Published

1988
1988
1997
1997

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 13 publications
1
19
0
2
Order By: Relevance
“…Qualitative comparison of the flavonoid aglycones in propolis and bud secretions of different tree species has indicated that in the European part of Russia propolis has been collected mainly from Betula verrucosa bud secretions (Popravko, 1976), in the Ukraine -from Betula verrucosa, Populus nigra and P tremula bud secretions (Popravko and Sokolov, 1980), in France (Lavie, 1976), Great Britain (Greenaway et al, 1987), Hungary (Papay et al, 1986), and even in the Sonoran Desert, Mexico (Wollenweber et al, 1987) from poplar bud secretions. More chemical evidence is needed regarding reports from other parts of the world claiming that propolis can be collected from many other sources (Koenig, 1985 (Popravko and Sokolov, 1980 In Bulgarian propolis we found 21 phenolic compounds of the 24 found in P italica bud secretions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative comparison of the flavonoid aglycones in propolis and bud secretions of different tree species has indicated that in the European part of Russia propolis has been collected mainly from Betula verrucosa bud secretions (Popravko, 1976), in the Ukraine -from Betula verrucosa, Populus nigra and P tremula bud secretions (Popravko and Sokolov, 1980), in France (Lavie, 1976), Great Britain (Greenaway et al, 1987), Hungary (Papay et al, 1986), and even in the Sonoran Desert, Mexico (Wollenweber et al, 1987) from poplar bud secretions. More chemical evidence is needed regarding reports from other parts of the world claiming that propolis can be collected from many other sources (Koenig, 1985 (Popravko and Sokolov, 1980 In Bulgarian propolis we found 21 phenolic compounds of the 24 found in P italica bud secretions.…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with our earlier observations that antibacterial activity of Mongolian propolis is higher than that of Bulgarian propolis . It is evident that under different ecological conditions: in desert regions (Sonoran Desert, Mexico (Wollenweber et al, 1987) (Ghisalberti, 1979 …”
Section: Introductionmentioning
confidence: 99%
“…Coll The phenolic portions of ground propolis sam ples were extracted with acetone and with warm ethanol, respectively. Flavonoid aglycones were identified by direct TLC comparison with markers, based on the senior author's experience with the analysis of flavonoid aglycones in general, and with poplar bud exudates and with propolis in par ticular (Wollenweber, 1975;Wollenweber et al, 1987a;Wollenweber et al, 1990). Propolis samples and plant exudates were also compared directly by TLC.…”
Section: Methodsmentioning
confidence: 99%
“…A study of the flavonoid aglycones of these samples revealed that even in that region the bees must have access to poplar trees, as the propolis flavonoid patterns were typical for Popu lus bud exudates (Wollenweber and Egger, 1971;Wollenweber, 1975;Wollenweber et al, 1987a (Benson and Darrow, 1981). The "fingerprint" of these propolis samples matches with bud exudate of P. fremontii, although this poplar is extremely rare in the Tucson area where it grows only spo radically in watercourse beds .…”
Section: Introductionmentioning
confidence: 99%
“…therein), for Prunus (Rosaceae, [4]), and for Rhamnus (Rhamnaceae, [4]). Some more recent results were reported and concerned rare flavonoid aglycones in Betula nigra [5], phenolic triglycerides in Popu lus lasiocarpa [6], cinnamic acid derivatives in Populus nigra [7], and a stilbene in Alnus viridis [8], In the course of these studies, several minor prod ucts remained unidentified, due to paucity of ma terial and/or lack of markers. After isolation by preparative TLC, some of these have been identi fied by direct comparisons with authentic samples; one structure was elucidated by N M R analysis.…”
Section: Introductionmentioning
confidence: 99%